Study of Solvent and Catalyst in Diimide Biphasic Hydrogenation System of Natural Rubber - Dody Andi Winarto; Chandra Liza; Mohamad Irfan Fathurrohman; Abdulhakim Masa; Mochamad Chalid (International Journal of Technology, 2024)
In Indonesia, solid rubber is the most common form of natural rubber (NR) intermediates because it is easy to store and transport. However, hydrogenation, a process aimed at improving the quality of NR by addressing its vulnerability to environmental factors due to the presence of carbon double bonds, is typically carried out under relatively mild conditions using latex material. This study explores a biphasic hydrogenation approach using solid NR dissolved in a solvent and a hydrogen source (hydrazine hydrate and hydrogen peroxide) mixed in water. The choice of solvents, catalysts, and the water-to-solvent volume ratio were examined for their impact on hydrogenation. Characterization was conducted using Fourier Transform Infrared (FTIR) spectroscopy as a qualitative indicator of hydrogenation. Meanwhile, Nuclear Magnetic Resonance 1H-NMR spectroscopy is used to measure the degree of hydrogenation. The results indicate that partial hydrogenation was successful using toluene as a solvent and ethylene diamine tetra acetic acid diammonium copper (Cu-EDTA) as a catalyst, with variations in water volume influencing the degree of hydrogenation. A degree of hydrogenation of 7.69% was achieved using 15 mL of water. The thermal properties of hydrogenated NR remain comparable to the original material, with improved heat resistance. This biphasic hydrogenation method offers the potential to enhance the properties of NR in various applications.